[Just once ; Brother right or wrong; Bringing back EDSA [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1991)
James Ingram concert in the Philippines and his well loved music; the death of Lenny Villa during a fraternity initiation; Anniversary of the EDSA revolution.
Just once (15 min.) -- Brother right or wrong (25 min.) -- Bringing back EDSA (15 min.)
VHS.
Reporter, Luchi Cruz-Valdes.
Keywords: Ingram, James; Villa, Leonardo Hernandez; Aquila, Legis Fraternity; Popular music -- United States; Philippines -- History -- Revolution, 1986.